Sunset lives : British retirement migration to the Mediterranean - King, Russell, 1945-; Warnes, A. M.; Williams, Allan M. (Oxford : Berg, 2000)
An analysis of the phenomenon of international retirement migration, this traces the story of the migrants from their old to their new homes, and examines the conceptual and policy contexts of this relatively new form of transnational mobility.
1. Retirement Abroad -- 2. International Retirement Migration and its Southern European Dimension -- 3. The Importance of Place: Contrasting Areas for Retirement Migration in Southern Europe -- 4. Who Migrates? International Retirement Migration as a Socially Selective Process -- 5. The Siren's Call: The Migration Decision -- 6. Living Abroad: Language, Social Activities and Integration -- 7. Retirement Abroad and Health and Welfare -- 8. Impacts and Prospects.
Includes bibliographical references and index.
Keywords: British -- Mediterranean Region; Retirees -- Great Britain; Mediterranean Region -- Emigration and immigration; Great Britain -- Emigration and immigration